2022
DOI: 10.1097/yco.0000000000000841
|View full text |Cite
|
Sign up to set email alerts
|

Update on treatments for anxiety-related disorders

Abstract: Purpose of reviewThis review examines recent evidence that informs the treatment of anxiety-related disorders.Recent findingsIn addition to selective serotonin reuptake inhibitors (SSRIs), serotonin and norepinephrine reuptake inhibitors (SNRIs), and benzodiazepines, agomelatine has demonstrated efficacy in treating generalized anxiety disorder (GAD). Other novel products, such as ketamine, psilocybin and cannabidiol, are in the process of gathering evidence in support of the treatment of anxiety disorders. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…The findings showed that the AOE exerted its anxiolytic and antidepressant actions through the possible participation of the GABAergic and noradrenergic systems, respectively. An impairment in the noradrenergic system is involved in developing depression and anxiety [ 35 ]. Imipramine, desipramine, protriptyline, and others are antidepressant drugs that act through the noradrenergic system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings showed that the AOE exerted its anxiolytic and antidepressant actions through the possible participation of the GABAergic and noradrenergic systems, respectively. An impairment in the noradrenergic system is involved in developing depression and anxiety [ 35 ]. Imipramine, desipramine, protriptyline, and others are antidepressant drugs that act through the noradrenergic system.…”
Section: Discussionmentioning
confidence: 99%
“…Imipramine, desipramine, protriptyline, and others are antidepressant drugs that act through the noradrenergic system. Lofepramine, a noradrenaline uptake inhibitor, is used to decrease the number of panic attacks [ 35 , 36 ]. The noradrenergic system is a therapeutic target for anxiety and depression [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations in serotonin 5-HT levels have been shown to substantially impact anxiety-related behaviors ( Riedel et al, 2002 ; Pobbe et al, 2011 ; Zangrossi and Graeff, 2014 ), while SSRIs have emerged as first-line therapy for anxiety (H. J. Lee and Stein, 2023 ). SNRIs, also employed as first-line clinical agents, imply an effect of NE on mood.…”
Section: Discussionmentioning
confidence: 99%
“…Response to standard pharmacological or psychological treatments in anxiety and stress-related disorders is often unsatisfactory ( 5 , 6 , 33 ). Non-invasive neurostimulation methods, such as repetitive transcranial magnetic stimulation (rTMS) and transcranial direct current stimulation (tDCS) have shown preliminary evidence of efficacy in anxiety disorders and PTSD ( 34 ). Chang et al describe the successful use of accelerated theta-burst rTMS, applied over the dorsolateral prefrontal cortices (DLPFC), in a patient with treatment-resistant PTSD occurring in the context of emotional and physical abuse.…”
mentioning
confidence: 99%